2018
DOI: 10.1177/1065912918796314
|View full text |Cite
|
Sign up to set email alerts
|

TRENDS: How Does Partisanship Influence Policy Diffusion?

Abstract: We explore the role of partisanship in policy diffusion. Previous studies suggest that partisanship may influence the willingness of public officials to learn from the experience of their peers. Officials’ willingness to consider policies endorsed by copartisans can arise either because party labels are used as informational cues or simply due to copartisan imitation. In the latter case, knowing more about the policy trade-offs should have no effects on politicians’ preferences. Based on two experiments with l… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1
1

Citation Types

1
11
0

Year Published

2020
2020
2024
2024

Publication Types

Select...
6
2

Relationship

1
7

Authors

Journals

citations
Cited by 15 publications
(12 citation statements)
references
References 39 publications
1
11
0
Order By: Relevance
“…Given their cognitive limitations and biases, policymakers process outside information selectively, paying particular attention to policies believed compatible with their own worldviews. A growing body of work has found that diffusion is conditional on ideology (Grossback et al 2004;Martin 2010;Butler et al 2017;Butler and Pereira 2018). Simply put, faced with uncertainty over the consequences of a new policy, left-wing policymakers will be more attracted to policies previously adopted by other left-wing governments and skeptical of policies associated with right-wing governments and vice versa.…”
Section: Conditional Diffusion: the Role Of Ideologymentioning
confidence: 99%
See 2 more Smart Citations
“…Given their cognitive limitations and biases, policymakers process outside information selectively, paying particular attention to policies believed compatible with their own worldviews. A growing body of work has found that diffusion is conditional on ideology (Grossback et al 2004;Martin 2010;Butler et al 2017;Butler and Pereira 2018). Simply put, faced with uncertainty over the consequences of a new policy, left-wing policymakers will be more attracted to policies previously adopted by other left-wing governments and skeptical of policies associated with right-wing governments and vice versa.…”
Section: Conditional Diffusion: the Role Of Ideologymentioning
confidence: 99%
“…The Cases of Costa Rica, Bolivia, and Argentina The previous chapter argued that the correlation between presidential ideology and conditional cash transfer program design is explained by the tendency of politicians to emulate policies that had already been tried by those in their ideological peer group (Grossback, Nicholson-Crotty, and Peterson 2004;Martin 2010;Butler et al 2017;Butler and Pereira 2018). Specifically, it was argued that left-wing leaders emulated the Brazilian left's basic income CCT while center and right-wing governments emulated the Mexican right's human capital program, which was actively promoted by the World Bank and the Inter-American Development Bank.…”
Section: Presidential Ideology's Effect On Cct Adoption and Designmentioning
confidence: 99%
See 1 more Smart Citation
“…Resource constrained policymakers use states’ ideological leanings as an informational shortcut (Grossback, Nicholson-Crotty, and Peterson 2004; Shipan and Volden 2008; Volden 2006). Drawing on experimental data, Butler and Pereira (2018) found officials expressed more interest in learning about a policy if it was endorsed by co-partisans in other jurisdictions. In a related study, Butler et al (2017) found officials ideologically predisposed against a policy expressed less interest in learning from others.…”
Section: The Conditional Nature Of Policy Learningmentioning
confidence: 99%
“…In addition to testing the effect of political behavior, I control for other state government preferences. Berry et al (1998), Shipan & Volden (2006), McCann et al (2015, and Butler & Pereira (2018) suggest that more activist and more liberal governments are more likely to pass laws and enact smoking restrictions. In this sense, I expect that, when both legislative chambers have Democratic majorities, the most liberal government will adopt the policy.…”
mentioning
confidence: 99%